Determining Factors of Financial Performance Recovery in BRI During the Covid-19 Pandemic - Damiana Noor Firdauza; Yan Rahadian (Economics Development Analysis Journal, 2022)
Bank Rakyat Indonesia (BRI) succeeded in loan restructuring in the Micro Small Medium Enterprises (MSMEs) segment. Loan restructuring has succeeded in pushing BRI to achieve the highest financial performance. This study aims to determine the success factors of BRI's loan restructuring. The research object is the Credit Restructuring and Recovery Division. This study applies a qualitative case study. Interviews and documentation were used to collect the data. The findings indicate that the critical success factor in dealing with the crisis is ability to adapt to policies change. The debtor's criteria and loan restructuring cycle are critical success factors of BRI's loan restructuring before the restructuring policy is set. The combination of three main components, namely interest rates, extending loan terms, and payment delays, are a determining factor for the success of loan restructuring. There are five components that support the success of loan restructuring, namely loan marketing, loan guarantee, personal values, information and communication, and other party cooperation.